On the mathematical theory of microstructure evolution during final stage of liquid phase sintering - Golovchan, V.T. (Сверхтвердые материалы, 2014)
A new mathematical theory of the microstructure evolution during the final isothermal stage of liquid phase sintering has been developed. The basis of this theory has been formed by materials science and continuum mechanics. The microstructure evolution has been described by the system of non-linear differential equations, which contain more than ten parameters. Finite difference analysis has been performed for a heavy alloy cylindrical specimen. The results of the calculations have been compared with experimental data.